2021
DOI: 10.1371/journal.pone.0259454
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome profile of hospitalized African patients with COVID-19: The Ethiopian context

Abstract: Background The COVID-19 pandemic seems to have a different picture in Africa; the first case was identified in the continent after it had already caused a significant loss to the rest of the world and the reported number of cases and mortality rate has been low. Understanding the characteristics and outcome of the pandemic in the African setup is therefore crucial. Aim To assess the characteristics and outcome of Patients with COVID-19 and to identify determinants of the disease outcome among patients admitt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
6
25
0
Order By: Relevance
“…Furthermore, patients with comorbidity tend to be older, that in-turn adds to the existing decrease in immunity. This finding is also supported by other studies conducted in Ethiopia, China, England and the US [ 5 , 12 , 26 , 27 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, patients with comorbidity tend to be older, that in-turn adds to the existing decrease in immunity. This finding is also supported by other studies conducted in Ethiopia, China, England and the US [ 5 , 12 , 26 , 27 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 88%
“…This implies that non-respiratory symptoms also might have a predictive value in disease categorization. This is also demonstrated by other studies in Ethiopia [ 4 , 5 , 24 26 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is in contrast to a study conducted in United Kingdom and North America where mortality rate of 1% and 4% were reported, respectively [ 4 ]. This also shows that the disease might have a different pattern compared to adults as a study conducted at our center among adults reported a mortality rate of 5.3% [ 23 ]. This difference could be attributed to the large proportion of asymptomatic patients in the studied population and also the small sample size in our study.…”
Section: Discussionmentioning
confidence: 87%